Association of Deha Prakṛti (Body Constitution) with Expression of Selected Inflammatory Markers in Patients with Chronic Kidney Disease (CKD) - Western Province, Sri Lanka (International Journal of Ayurveda and Pharma Research, 2024)
Deha prakṛti is a fundamental concept in Āyurveda, offers a promising approach to prevent and manage Chronic Kidney Disease (CKD) through an integrated perspective. While Deha prakṛti is widely recognized for its applications in predicting disease susceptibility, facilitating early detection, guiding treatment plan and influencing dietary and behavioral patterns, there is a notable gap in scientific evidence supporting its associations with various aspects of chronic disorders such as CKD. One such aspect is the immunological impairment in CKD patients, which is a significant concern that needs to be addressed immediately and no scientifically proven studies found in relation to the above in previous literature. In order to address this research gap, present study investigated the relationship between Deha prakṛti and specific inflammatory markers- namely Erythrocyte Sedimentation Rate (ESR), C- Reactive Protein (CRP), Interleukin-6 (IL-6) and Tumor Necrosis Factor-alpha (TNF-α) in CKD patients, Western Province, Sri Lanka. An assessment of the association between Deha prakṛti and the expression of selected inflammatory markers in CKD patients would provide insights to successfully manage the disease by developing targeted treatment modalities focusing on inflammatory markers. The study involved 113 diagnosed CKD patients and their Deha prakṛti type was assessed using ĀyuSoft software. ESR and CRP levels were determined according to the Westergren method and CRP latex slide agglutination method respectively, while IL-6 and TNF-α levels were quantitatively measured using Enzyme Linked Immunosorbent Assay (ELISA) based on the sandwich principle. It was observed that the types of Deha prakṛti in CKD patients are significantly associated with the levels of ESR and IL- 6 indicating that the levels of ESR and IL - 6 inflammatory markers depend on the types of Deha prakṛti in CKD patients. However, it was also noticed that the types of Deha prakṛti were not significantly associated with the levels of CRP and TNF-α. This will lead the Āyurveda physicians to plan and develop specific treatment regimens with accurate drug dosage and dietary - behavioral patterns targeting the above inflammatory markers related to the Dehaprakṛti types of the CKD patients. Since it was also observed that CKD patients with Pitta and Vāta pradhāna prakṛti types are more susceptible to elevated levels of inflammatory markers, it is advisable to implement precautions during the early stages of the disease based on the specific type of Deha prakṛti in order to prevent the progression of the disease to End stage Renal Disease (ESRD).